2021
DOI: 10.3390/w13121702
|View full text |Cite
|
Sign up to set email alerts
|

Projecting Relative Sea Level Rise under Climate Change at the Phrachula Chomklao Fort Tide Gauge in the Upper Gulf of Thailand

Abstract: This study aims to project future sea-level rise (SLR) at the Phrachula Chomklao Fort (PCF) tide gauge station in the Upper Gulf of Thailand (UGoT) using the outputs of 35 climate models under two greenhouse gas concentration scenarios: representative concentration pathway 4.5 (RCP4.5) and RCP8.5. The Linear Scaling method was found to be better than Variance Scaling and Quantile Mapping methods for removing biases in raw Global Circulation Models (GCMs) sea level data. Land subsidence, induced by excessive gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
3
3
0
Order By: Relevance
“…These results are consistent well with previous studies based on tidal gauge and satellite altimetry data demonstrated that the sea level in the Gulf of Thailand and the Andaman Sea has been rising significantly faster than other parts of the Indian and Pacific oceans [51][52][53][54][55][56]. Land subsidence due to excessive groundwater extraction and earthquakes was found to be the main contributor to such a high rise [52][53]57]. By comparison, the average rate of sea level rise in the Andaman Sea was higher than that in the Gulf of Thailand (Fig.…”
Section: Sea Level Rise and Seawater Intrusionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are consistent well with previous studies based on tidal gauge and satellite altimetry data demonstrated that the sea level in the Gulf of Thailand and the Andaman Sea has been rising significantly faster than other parts of the Indian and Pacific oceans [51][52][53][54][55][56]. Land subsidence due to excessive groundwater extraction and earthquakes was found to be the main contributor to such a high rise [52][53]57]. By comparison, the average rate of sea level rise in the Andaman Sea was higher than that in the Gulf of Thailand (Fig.…”
Section: Sea Level Rise and Seawater Intrusionsupporting
confidence: 92%
“…Salinity at the Samlae pumping station of water supply for Bangkok and its surrounding provinces, which is approximately 96 km upstream of the mouth of the Chao Phraya River, exhibits an increasing trend with statistical significance at a 95% confidence level. Our results are consistent with the observed situation in early 2020 when salt water climbed up the Chao Phraya River and reached the city's main municipal water intake, threatening the quality of the raw water supply [57,[66][67]. Seawater intrusions have frequently occurred in the Gulf of Thailand due to the low-lying area's proximity to the sea and the combined effects of sea level rise, deep well pumping and land subsidence [57,[66][67].…”
Section: Sea Level Rise and Seawater Intrusionsupporting
confidence: 90%
See 2 more Smart Citations
“…1). In this region, sea level may rise as much as 60 cm until the end of the twenty-first century (Oppenheimer et al, 2019), depending on the global warming scenario used for simulations (Jaroenongard et al, 2021). Such predictions are supported by tide gauge data (Sojisuporn et al, 2013) revealing a sea-level increase of about 5 mm/yr for the period AD 1985–AD 2009, in a similar range as altimetry measurements (Trisirisatayawong et al, 2011).…”
Section: Regional Settingmentioning
confidence: 99%